CURRENT STAGE OF THE EUPOLITICAL AND ECONOMIC INTEGRATION– HOW TO SETTLE THE “ANTIQUE UTILIZATION” DILEMMA? - Vitkus, Gediminas (Politologija, 2015)
Although the EU has passed a long way and implemented a lot of impressive projects, previous merits were not sufficient for permanent and unconditional public confidence and support. People continue to expect from the EU more and more impressive achievements, regardless of its limited potential. In other words we are facing a sort of the “antique utilization”dilemma, which arises for people, who are already bored previously considered valuable items. However, it seems nobody is seriously considering how to get rid of this useless-looking item. Vice versa, there is no shortage of ideas and proposals how to remake the EU. Two main alternatives could be discerned out of recent discussions and debates. The first alternative is a “federalist”one. It proposes the EU to continue transformation along the lines of federal democratic state model. However this alternative looks groundless since rulings elites of the member states don’t look ready to transfer more power to the European institutions. The second alternative aroused with the context of constructivism and rationalism debate. It suggests the EU instead of trying to become more nation-state alike, to transform itself to the new kind of polity with decentralized, unenforced and voluntarily governance of European nations. However this kind of alternative suffers from indeterminacy. It is too difficult to “translate”it into the legal language of international treaties and legislation. Hence, since the both alternatives do not like viable, it looks like that the “antique utilization”dilemma is going to persist as a trouble maker without clear solution in foreseeable future.